Effectiveness of mifepristone versus balloon catheter in induction of labour in women with previous caesarean sections: a randomised comparative study - Tomar, Yugantika; Najam, Rehana; Singh, Mrinalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Termination of pregnancy is a stressful situation for the patient specially due to increasing trend of caesarean sections (CS) wherein due to risk of scar rupture a repeat caesarean is advocated by many practitioners. Especially in these cases vaginal delivery should be preferred over CS to avoid the added stress of a major surgery to the woman which increases the risk of scar rupture and adhesions in subsequent pregnancies. Hence the aim was to compare the safety and effectiveness of mifepristone versus balloon catheter in termination of pregnancy in women with previous CS. Methods: Prospective randomized comparative study was done at obstetrics and gynaecology department of Teerthankar Mahaveer medical college and research centre, Moradabad UP from January 2020 to July 2021. 60 subjects were randomised into 2 groups by the envelope method. Results: The mean bishops score at 36 hours was found to be 10.2±1.25 and 9.81±1.54 in groups M and B respectively. No statistically significant difference was found between the bishops score of the two groups at 24 and 36 hours. Patients induced with mifepristone had significantly longer induction delivery, Induction augmentation and Induction-labour intervals. However, these patients ultimately had more number favourable outcomes in terms of vaginal delivery, although not statistically significant. Conclusions: Foleys insertion is an invasive and painful process and more uncomfortable for the patient. Mifepristone can safely be used in place of foleys catheter for induction of labour in patients with previous 1 CS.